Atomic Layer Deposition ZnO-Enhanced Negative Electrode for Lithium-Ion Battery: Understanding of Conversion/Alloying Reaction via 7Li Solid State NMR Spectroscopy. Issue 1 (1st January 2023) - Sadighi, Zoya; Price, Jeffrey S.; Qu, Jingyi; Emslie, David J. H.; Botton, Gianluigi A.; Goward, Gillian R.
Abstract : Understanding the mechanism for capacity delivery in conversion/alloying materials (CAM) electrodes, such as ZnO, in lithium-ion batteries (LIBs) requires careful investigation of the electrochemical reactions. Here, we used magic angle spinning (MAS at 60 kHz) 7 Li nuclear magnetic resonance (NMR) as a sensitive analytical means to probe the reactions occurring between electrode materials and Li + ions. The ZnO nanolayer generated on carbon substrate by atomic layer deposition (ALD) enhanced the cyclic capacity of half cell LIB up to 40%. 7 Li NMR revealed Lix Zn alloy formation through an irreversible conversion reaction during discharge. MAS results revealed the dealloying of Lix Zn at the full charge step which left atomic zinc nanograins that do not undergo the re-oxidation of zinc atoms according to the cyclic voltammetry. An in situ formation of elemental zinc at the initial cycles facilitates uniform lithium deposition on subsequent cycles due to the reduced energy barrier for lithium nucleation on pure zinc as compared to ZnO. X-ray diffraction analysis indicated the crystalline formation of the Lix Zn alloy while scanning electron microscope showed the uniform morphology for the lithiated discharge products. Cyclic voltammetry and differential capacity functions initially predicted the conversion and alloying reactions.